Seeing Domestic and Industrial Logistic in Context of CO2 Emission: Role of Container Port Traffic, Railway Transport, and Air Transport Intensity in Thailand - Tarasawatpipat, Chaisri; Srimarut, Thammarak; Mekhum, Witthaya (International Journal of Energy Economics and Policy, 2020)
CO2 emission has becoming a global issue with its increasing intensity and quantity. There are various factors that have been found that affect CO2 emission positively or negatively. In this study, the author has selected three independent variables i.e. container port traffic, railway transport and air transport intensity so that their impact can be studied on CO2 emission. The author has gathered data from Thailand in context of the above-mentioned variables for 27 years. After application of several tests and approaches such as unit root tests, co-integration test and VAR model estimation, the results of these approaches have been obtained. The order of integration, scholastic properties, co-integrated relationships and short and long run relationships have been explored by the use of these approaches. According to these results, the impact of all the independent and control variables have been found as significant on CO2 emission. After the detailed discussion of results obtained by the author, some of the benefits related to this study have been discussed. These benefits may be for many people such as researchers, government and other authorities. Keywords: Domestic and Industrial Logistic, CO2 Emission, Container Port Traffic, Railway Transport, Air Transport Intensity JEL Classifications: L92, L93 DOI: https://doi.org/10.32479/ijeep.10227